Cost of status epilepticus: A systematic review. (January 2015) - Kortland, Lena-Marie; Knake, Susanne; Rosenow, Felix; Strzelczyk, Adam
Highlights: There is a paucity of data on the costs of SE with only two published studies. SE is a cost-intensive disorder with an acute CNS aetiology as main cost-driving factor. Mean hospital costs are US18, 834 (USA) and €8347 (Germany) per admission. Annual direct costs are projected at US4 billion (USA) and at €83 million (Germany). Abstract: The objective of this review is to give an overview of published cost of illness (COI) studies on status epilepticus (SE). For identifying COI studies that evaluated the direct and indirect costs of SE, a systematic literature review was performed. We used a standardized assessment form for extracting information on the study design, methodological framework, and data sources from each publication. The results were systematically reported. We identified only two studies worldwide, which included prevalence- or incidence-based data on the direct costs of SE: one from Germany and one from the USA. Both used a bottom-up approach and a prospective design. The estimated mean inpatient costs summed up to US18, 834 in the USA and to €8347 in Germany per admission with an average length of stay of 12.9 and 14.0 days. The mean annual direct costs for SE had been estimated at US4 billion in the USA and at €83 million (adults only) in Germany. Both available studies indicate that SE is a cost-intensive disorder with an acute CNS aetiology as a cost-driving factor. In conclusion, there is a paucity of data on the costs of SE. Further studies are warranted to determine costs, its predictors, quality of life, mortality data due to SE and its sequelae and to provide a basis for further cost-effectiveness calculations for new drugs and other interventions in SE and prolonged seizures.